Deletion of the CYP2D6 gene as a likely explanation for the serious side effects of the antipsychotic drug pimozide: a case report - Facal, Fernando; Portela, Begoña; Gil-Rodríguez, Almudena; Barros, Francisco; Maroñas, Olalla; Carracedo, Angel (Frontiers in Pharmacology, 2023)
CYP2D6 analysis prior to the prescription of pimozide is required above a certain dose by the Food and Drug Administration in order to detect individuals with the poor metabolizer status. This precautionary measure aims to prevent the occurrence of serious adverse drug reactions. This study presents a case of a patient diagnosed with schizophrenia spectrum disorder. The patient suffered re-admission in the psychiatry ward because of severe secondary symptoms due to the antipsychotic drug pimozide, previously prescribed on a first admission. In order to assess the patient’s medication profile, real-time PCR was performed to analyze the main genes responsible for its metabolization, namely, CYP2D6 and CYP3A4. The pharmacogenetic study revealed that the patient is a poor metabolizer for CYP2D6, presenting deletion of both copies of the gene (diplotype *5/*5). Fortunately, the symptomatology disappeared after the withdrawal of the responsible drug. In conclusion, abiding by the pharmacogenetic clinical practice guidelines and the pharmacogenetic analysis of CYP2D6 when prescribing pimozide would have probably saved the patient from the consequences of severe side effects and the health system expenditure. There is an important need for more training in the pharmacogenetic field for specialists in psychiatry.